2018
DOI: 10.1108/bfj-09-2017-0484
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and potential virulence of Escherichia coli in ready-to-eat raw mixed vegetable salads in collective catering in Abidjan, Côte d’Ivoire

Abstract: Purpose Vegetable salads, despite their recognized health benefits, are an increasingly common cause of foodborne illness worldwide. The purpose of this paper is to determine the prevalence of E. coli with virulence genes in ready-to-eat raw mixed vegetable salads sold in collective catering in Abidjan. Design/methodology/approach A total of 436 strains of E. coli were isolated from 306 ready-to-eat raw mixed vegetables salads and then identified biochemically and molecularly based on the uidA gene responsib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…No women have received training on good hygiene and manufacturing practices (GHMP). Difficulties related to non-compliance with GHMP may be due to a lack of information, training, qualification, and awareness [5] , [30] , [31] , [32] , [33] , [34] , [35] , [36] . In addition, the storage conditions of raw materials and prepared food have shown that only in one private school refrigeration is used to preserve unsold prepared food.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No women have received training on good hygiene and manufacturing practices (GHMP). Difficulties related to non-compliance with GHMP may be due to a lack of information, training, qualification, and awareness [5] , [30] , [31] , [32] , [33] , [34] , [35] , [36] . In addition, the storage conditions of raw materials and prepared food have shown that only in one private school refrigeration is used to preserve unsold prepared food.…”
Section: Discussionmentioning
confidence: 99%
“…The food preparation environment is improper, hygiene and manufacturing rules are not followed (poorly cleaned kitchen equipment). This situation would promote the development of pathogenic microorganisms that could subsequently contaminate food and make it unfit for consumption [ 5 , 10 , 23 , 36 , 43 ]. It is therefore crucial that the operators of food intended for school children must be trained in good hygiene and manufacturing practices to avoid contamination of food by pathogenic germs to ensure food safety for school children.…”
Section: Discussionmentioning
confidence: 99%
“…Enterobacteriaceae were the main bacteria contaminating the vegetables. The prevalence was 100%, 77.8% and 2.6% for Enterobacteriaceae, Escherichia coli and Salmonella sp., respectively [35]. The presence of Enterobacteriaceae in raw vegetable salads can be explained by the fact that they are widespread and widely distributed in the environment via soil, water, animal and human intestines, and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in Brazil, South Korea and Egypt reported the presence of ETEC in fish and seafood [14,15,16]. In Côte d'Ivoire, Kambire et al [17] andToe et al [18] reported a predominance of ETEC pathotype in the Aby Lagoon and vegetable salads respectively. ETEC strains are associated with two major clinical syndromes: child diarrhea in developing countries and traveller's diarrhoea (Turista) [19].…”
Section: Genesmentioning
confidence: 95%